SUSTAINABLE PRODUCTION FROM A DIRECT AID FUND FOR SMALL SILK PRODUCERS IN THE FRAMEWORK OF SILK PROJECT EUROPE AID LA/2016/378-553 - Marino, Patricia; Pujol, Rocio; Pescio, Francisco; Suarez, Eugenia; Sicari, Oscar; Zunini, Hernan; Enciso, Carlos (Fibernamics, 2021)
Silk is an important natural fiber and a resource for biomaterial. The SILK PROJECT focused on small-scale silk production in Latin America and Caribbean. It`s funded by the European Union through ADELANTE, a triangular cooperation programme. Along the project activities, a Development Support Fund was established to help local value in silk production chain, with sustainable practices and a gender perspective and biomaterials production. Also, three guide booklets were published oriented to sustainable sericulture within a circular economy focus. Actually, there are 30 experiencies in-work, which some of them are producing biomaterials, and three booklets online available.

Marino, Patricia.INTI. Argentina
Keywords: Textile process, silk fiber, sustainable practices, biomaterial, circular economy